(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article discusses various aspects of a child’s life in the family, and we can conclude how difficult it is to create ideal conditions in which individual characteristics of a developing preschool child’s personality will be taken into account. Because for the normal existence of a child, a mentally healthy child-parent relationship based on love and trust is necessary.